2014
DOI: 10.1002/ange.201407801
|View full text |Cite
|
Sign up to set email alerts
|

Direct Spectroscopic Evidence of Hyperconjugation Unveils the Conformational Landscape of Hydrazides

Abstract: International audienceThe stereochemistry of hydrazides makes them especially interesting as building blocks for molecular design. An exhaustive conformational analysis of three model hydrazides was conducted in a conformer-selective approach by using a combination of high-level quantum chemistry calculations and vibrational spectroscopy in the gas phase and in solution. The NH stretch frequency was found to be highly sensitive to hyperconjugation, thus making it an efficient probe of the conformation of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Comparison between experiments and theory is not only mandatory for proposing a basic interpretation, but is also at the heart of several of the most outstanding outcomes in the field. 72,74,103,113,133,134,141,144,150,152,153,[157][158][159][160]162,163,181,203,218,219,241,284,301,314,334,387,391,423,517 Nowadays, quantum chemistry suites are often sophisticated black boxes: even if an in-depth rationalization of the underlying phenomena is not easy to extract from calculations, they provide experimentalists with a reliable and relevant prediction of some of the experimental observables in the ground electronic state, like vibrational modes. The situation is more contrasted as far as the electronic structure and dynamical properties of the excited states of aromatic residues are concerned.…”
Section: Experimental Data Vs Theoretical Predictionsmentioning
confidence: 99%
“…Comparison between experiments and theory is not only mandatory for proposing a basic interpretation, but is also at the heart of several of the most outstanding outcomes in the field. 72,74,103,113,133,134,141,144,150,152,153,[157][158][159][160]162,163,181,203,218,219,241,284,301,314,334,387,391,423,517 Nowadays, quantum chemistry suites are often sophisticated black boxes: even if an in-depth rationalization of the underlying phenomena is not easy to extract from calculations, they provide experimentalists with a reliable and relevant prediction of some of the experimental observables in the ground electronic state, like vibrational modes. The situation is more contrasted as far as the electronic structure and dynamical properties of the excited states of aromatic residues are concerned.…”
Section: Experimental Data Vs Theoretical Predictionsmentioning
confidence: 99%
“…On the basis of the inputs obtained from the model systems containing OH, SH, and NH donors as well as O and S acceptors, it was extended to sulfur containing peptides to explore the role of SCHBs on local structures of the main chain induced by a Met or Cys residue. , The atomic scale information was obtained by gas phase spectroscopy of isolated model peptide chains. The approach was based on IR/UV double resonance spectroscopy of mass-selected jet-cooled molecules and their clusters, a technique very elegantly deployed on various model biomolecular systems as well as peptide chains. It was observed that sulfur atoms in the side chain of methionine and cysteine are capable of forming strong amide NH···S H-bonds. In the methionine containing peptides (e.g., AcPheMetNH 2 ; in short FM) NH···S H-bonds were surprisingly found to be the strongest among other H-bonds (NH···OC and NH···π H-bonds) .…”
mentioning
confidence: 99%
“…In general, there are two opposing hyperconjugation interactions which affect the C=O stretching frequency of the ester carbonyl group . Additionally, the n→π* interaction, which is present only in the cis conformer but not in the trans conformer of PhOAc or PhOF, can affect the hyperconjugation interactions and hence the C=O stretching frequency.…”
Section: Resultsmentioning
confidence: 99%